"BENEFITS OF USING MIND MAPS IN SCHOOL" - Djumayeva Feruza Tulkunovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: Mind mapping is a visual learning tool that enhances students’ comprehension, memory retention, and creativity. This article explores the benefits of using mind maps in educational settings, including improved critical thinking, better note-taking, and enhanced writing skills. By analyzing scholarly research and expert opinions, this paper highlights how mind maps can transform traditional teaching methods into dynamic, engaging learning experiences.